Spatial-temporal variations of the gas hydrate stability zone and hydrate accumulation models in the Dongsha region, China - Song, Yingrui; Lei, Yuhong; Zhang, Likuan; Cheng, Ming; Miao, Laicheng; Li, Chao; Liu, Naigui (Frontiers in Marine Science, 2022)
It is of great significance to study the spatial-temporal variations of the thickness of the gas hydrate stability zone (GHSZ) to understand the decomposition, migration, accumulation and dissipation of gas hydrate, the corresponding relationship between bottom-simulating reflectors (BSRs) and gas hydrate, and the distribution of heterogeneous gas hydrate. We selected the Dongsha region in the South China Sea (SCS) as the research object to calculate the spatial-temporal variation of the GHSZ since 10 Ma, analyzed the main factors affecting the thickness of the GHSZ, discussed the dynamic accumulation processes of gas hydrate, and proposed an accumulation model of gas hydrate in the Dongsha region. The results show that the thicknesses of the GHSZ in the study area were between 0 m and 100 m from 10 to 5.11 Ma, and the relatively higher bottom water temperature (BWT) was the key factor leading to the thinner thickness of the GHSZ during this period. From 5.11-0 Ma, the thickness of the GHSZ gradually increased but showed several fluctuations in thickness due to changes in the geothermal gradient, seawater depth, BWT, and other factors. The decrease in the BWT was the main factor leading to GHSZ thickening from 5.11 to 0 Ma. The thicknesses of the GHSZ are between 110 m and 415 m at present. The present spatial distribution features show the following characteristics. The GHSZ in the deep canyon area is relatively thick, with thicknesses generally between 225 m and 415 m, while the GHSZ in other areas is relatively thin, with thicknesses between 110 m and 225 m. Based on the characteristics of the GHSZ, two hydrate accumulation models are proposed: a double-BSRs model due to thinning of the GHSZ and a multilayer hydrate model due to thickness changes of the GHSZ, with single or multiple BSRs.